KEKUATAN PEMBUKTIAN SURAT KETERANGAN JUAL BELI SEBAGAI DASAR KEPEMILIKAN HAK ATAS TANAH (Studi Putusan Pengadilan Negeri Surakarta Nomor : 153/Pdt.G/2010/PN.Ska) - , Nonie Kusuma Dewi; , Kunthoro Basuki, S.H., M.Hum., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was intended to analyze proving power of sale certificate as base on ownership of right on land base on decree number : 153/Pdt.G/2010/PN.Ska and to analyze legal standing of right on land in which its certificate has been issued based on decree number : 153/Pdt.G/2010/PN.Ska. It is normative law research. It was conducted by studying literary material or secondary data consisting of primary law material and secondary law material related to research object. Data was collected using content analysis that discover meaning contained in a text and get understanding on message represented. Based on result and discussion, following conclusions were drawn. First, sale-purchase document has perfect proving power when content and signature in the deed is acknowledged by parties and has free proving power when any party denied it. In case of decision of Surakarta District Court number 153/Pdt.G/2010/PN.Ska, defendants did not deny sale-purchase documents presented by plaintiff. In civil law procedure, term not deny means acknowledge, so the sale-purchase document have binding power. Second, land sale-purchase done privately is not valid according to GR no. 24/1997. In case between plaintiff Pardiman Parto Diyono and defendants, plaintiff can use the decision of Surakarta District Court number 153/Pdt.G/2010/PN.Ska that has fix legal power as base for title transfer SHM no.175 from defendantsâ name to plaintiffâs name.